2013
DOI: 10.1021/es401841t
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Developmental Toxicity of New Aromatic Halogenated DBPs in a Chlorinated Saline Sewage Effluent to the Marine Polychaete Platynereis dumerilii

Abstract: Using seawater for toilet flushing may introduce high levels of bromide and iodide into a city's sewage treatment works, and result in the formation of brominated and iodinated disinfection byproducts (DBPs) during chlorination to disinfect sewage effluents. In a previous study, the authors' group has detected the presence of many brominated DBPs and identified five new aromatic brominated DBPs in chlorinated saline sewage effluents. The presence of brominated DBPs in chlorinated saline effluents may pose adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
340
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 507 publications
(353 citation statements)
references
References 45 publications
12
340
1
Order By: Relevance
“…Mammalian cell assay has shown that iodoacetic acid is 3 and 288 times more cytotoxic, and 2 and 47 times more genotoxic than bromoacetic acid and chloroacetic acid, respectively (Plewa et al, 2004). Most recently, it has been reported that I-DBPs present significantly higher developmental toxicity and growth inhibition than their brominated or chlorinated DBP analogues (Yang and Zhang, 2013;Liu and Zhang, 2014). Yang et al (2014) investigated toxic impact of bromide and iodide on drinking water disinfection and found that both cytotoxicity and genotoxicity were correlated with total organic iodine (TOI), but not to total organic chlorine (TOCl).…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian cell assay has shown that iodoacetic acid is 3 and 288 times more cytotoxic, and 2 and 47 times more genotoxic than bromoacetic acid and chloroacetic acid, respectively (Plewa et al, 2004). Most recently, it has been reported that I-DBPs present significantly higher developmental toxicity and growth inhibition than their brominated or chlorinated DBP analogues (Yang and Zhang, 2013;Liu and Zhang, 2014). Yang et al (2014) investigated toxic impact of bromide and iodide on drinking water disinfection and found that both cytotoxicity and genotoxicity were correlated with total organic iodine (TOI), but not to total organic chlorine (TOCl).…”
Section: Introductionmentioning
confidence: 99%
“…There may be two reasons for this. One is that after reactions with more chlorine, these intermediate chlorinated aromatic DBPs might decompose to more aliphatic ones, leading to lower toxicity (Li et al, 2015;Liu and Zhang, 2014;Yang and Zhang, 2013). The second reason is that more chlorine promotes the transformation from N-DBPs to C-DBPs.…”
Section: The Roles Of Kmno 4 Preoxidation In Genotoxicity Productionmentioning
confidence: 99%
“…In case of bromate according to both the US and EU, the permissible level is 10 μg/L, and for chlorate and chlorite is 700 μg/L (USEPA 2006). Yang and Zhang (2013) reported the occurrence of brominated haloacetic acids, four new brominated DBPs such as 2,6-dibromo-4-nitrophenol, 2,4,6-tribromophenol, 3,5-dibromo-4-hydroxybenzaldehyde, and 3,5-dibromo-4-hydroxybenzoic acid and 5-bromosalicylic acid in chlorinated saline secondary and primary sewage effluents. Evidences have shown that brominated/iodinated DBPs generally are highly cytotoxic and genotoxic than their chlorinated analogs.…”
Section: Introductionmentioning
confidence: 99%